PARADIGMA PENGUKURAN KINERJA GURU RAUDHATUL ATHFAL (RA) BERPRESTASI DI YOGYAKARTA - Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2019)
This study was conducted to determine the performance paradigm of outstanding RA teachers in Yogyakarta so that they can be measured and become role models for other teachers, in the discussion the authors used the research method used in this study was descriptive qualitative with a psychological approach carried out directly to the subject under study , in order to obtain all data relating to the performance paradigm of outstanding RA teacher teachers so that in their measurement they are able to become role models for fellow teachers. Data collection uses interviews, documentation, and observation. Data analysis techniques include reducing data, presenting, drawing conclusions and verifying. The validity test of the data is done by triangulation technique.The results revealed that in order to improve the performance of these outstanding RA teachers, there were 6 (six) steps taken by outstanding RA teachers. First, knowing there are still shortcomings in performance, secondly recognizing weaknesses and shortcomings in the seriousness of teaching, thirdly identifying what is the cause of deficiencies, especially relating to the performance itself, fourth developing the presented performance plan, the fifth doing the assessment the problem has been resolved or not (problem solving), the sixth start again, if needed and needed again.